Biomonitoring of the responses of fish to environmental stress - Laitinen, Markku (1995)
Biomonitoring of stress responses in fish to water acidity was first conducted in relation to embryonic mortality and ion balance. In addition, fish behaviour, cardiac and ventilation rates recorded with non-contact bioelectronic monitoring equipment were used to quantify the effects of acidity and aluminium, handling stress and parasite infection. Embryonic mortality of perch, Perca fluviatilis inhabiting an acid lake was markedly higher than that of a neutral reference lake population. High mortality when reared in neutral water indicated a poorer quality of eggs produced by the acid lake perch. No changes were observed in milt quality. Elevation of water CaCl₂ and MgCl₂ concentration in acid water decreased embryonic mortality in the rainbow trout, Oncorhynchus mykiss. After hatching, the most marked effects of acid stress were the inhibition of Ca-, and less strongly Cl-intake, and yolk utilization of the fry. Five minute handling stress resulted in a short period of increased activity and more prolonged elevation of heart and ventilation rates, especially in fed brown trout. In trout acclimated for 7d to aquaria, the responses following 5 minutes physical disturbance did not markedly differ from a short move between aquaria or a move to acid (pH 4.7) water. Transfer to acid water following 5 minutes disturbance prolonged the recovery of fish. Exposure for 7 days to pH 4.7 alone and with aluminium (280 and 450 μg*1ˉ¹) increased heart and ventilation rates in brown trout, Salmo trutta. Especially ventilation rate remained higher in combination with aluminium. Based on both the terminal haematological and on-line biomonitoring data, the fish were experiencing hyperglycaemia in combination with respiratory stress. Exposures to cercariae of the digenean parasite, Diplostomum pseudospathaceum caused a dose-dependent increase in total activity of roach, Rutilus rutilus and brown trout, and an increase in heart and ventilation rates in brown trout, followed by a host-specific recovery time in the activity of fish.